Designing Ergonomic Standing Chair for Computer Numerical Control Machine Operators using TRIZ - Rizalulhaq Rasyid; Dino Caesaron; Yusuf Nugroho Doyo Yekti (International Journal of Innovation in Enterprise System, 2023)
In this research, the working hours and posture of CNC (Computer Numerical Control) machineoperators were investigated to determine the physical workload that they experienced during theirdaily work. Based on our observations, the operator works 8-hour regular shifts or 12-hour longshifts for 5 – 6 days a week. During these shifts, the operators work in front of the CNC machinewhile standing upright without any tools to rest. Preliminary research was conducted to evaluatethese conditions the results show 13 out of 20 CNC machine operators complained about physicalfatigue while working the CNC machines. It can also be concluded that the operators areexperiencing excessive workload based on a workload assessment using the Quick Exposure Check(QEC) method. To solve this problem, a standing chair is designed with ergonomics in mind. Thedimensions of the standing chair are based on the anthropometry of the CNC machine operators,which was never used before. The design process is conducted using the Theory of InventiveProblem Solving (TRIZ) methodology. Need statements from the CNC machine operators anddesign requirements from the stakeholders are converted into design specifications using TRIZmethodology. Parameters are determined to increase the capability of the existing design based onthe design specifications. The result of this research is a standing chair that is suitable for theoperator’s needs. Based on the analysis of the design result and the stress analysis simulation, it canbe concluded a functional standing chair can be ergonomically designed with the TRIZmethodology.